Determination of interfacial amorphicity in functional powders - Tejedor, Maria Badal; Nordgren, Niklas; Schuleit, Michael; Pazesh, Samaneh; Alderborn, Göran; Millqvist-Fureby, Anna; Rutland, Mark W. (Langmuir, 2017)
The nature of the surfaces of particles of pharmaceutical ingredients, food powders, and polymers is a determining factor for their performance in for example tableting, powder handling, or mixing. Changes on the surface structure of the material will impact the flow properties, dissolution rate, and tabletability of the powder blend. For crystalline materials, surface amorphization is a phenomenon which is known to impact performance. Since it is important to measure and control the level of amorphicity, several characterization techniques are available to determine the bulk amorphous content of a processed material. The possibility of characterizing the degree of amorphicity at the surface, for example by studying the mechanical properties of the particles' surface at the nanoscale, is currently only offered by atomic force microscopy (AFM). The AFM PeakForce QNM technique has been used to measure the variation in energy dissipation (eV) at the surface of the particles which sheds light on the mechanical changes occurring as a result of amorphization or recrystallization events. Two novel approaches for the characterization of amorphicity are presented here. First, since particles are heterogeneous, we present a methodology to present the results of extensive QNM analysis of multiple particles in a coherent and easily interpreted manner, by studying cumulative distributions of dissipation data with respect to a threshold value which can be used to distinguish the crystalline and amorphous states. To exemplify the approach, which is generally applicable to any material, reference materials of purely crystalline α-lactose monohydrate and completely amorphous spray dried lactose particles were compared to a partially amorphized α-lactose monohydrate sample. Dissipation data are compared to evaluations of the lactose samples with conventional AFM and SEM showing significant topographical differences. Finally, the recrystallization of the surface amorphous regions in response to humidity was followed by studying the dissipation response of a well-defined surface region over time, which confirms both that dissipation measurement is a useful measure of surface amorphicity and that significant recrystallization occurs at the surface in response to humidity. (Figure Presented).
Publisher Copyright: © 2017 American Chemical Society.